Enhancement of machinability of Inconel 718 in end milling through online induction heating of workpiece - Amin, A. K. M. Nurul; Hossain, Mohammad Ishtiyaq; Patwari, Anayet Ullah (Trans Tech Publications, Switzerland, 2012)
This paper presents the outcome of a study on heat assisted end milling of Inconel 718 using inducting heating technique conducted to enhance the machinability of the material. The heating temperature maintained below the phase transformation temperature was aimed at softening the top removable material layers. The experimental results of both conventional and heat assisted machining were compared. The machinability of Inconel 718 under these conditions was evaluated in terms of tool life, tool wear morphology and chatter. The advantages of Induction heating is demonstrated by an longer tool life and lower chatter. The study showed that preheated machining facilitates up to 80% increase of tool life over conventional machining conducted using TiAlN coated carbide inserts.